The Probability Distribution of Foreign Exchange Price Changes: Tests of Candidate Processes - Tucker, Alan L.; Pond, Lallon (The Review of Economics and Statistics, 1988)
Alan L. Tucker, Lallon Pond, The Probability Distribution of Foreign Exchange Price Changes: Tests of Candidate Processes, The Review of Economics and Statistics, Vol. 70, No. 4 (Nov., 1988), pp. 638-647